KEUNGGULAN SISTEM KEUANGAN BERBASIS BAGI HASIL DAN IMPLIKASINYA PADA DISTRIBUSI PENDAPATAN - Iman Sugema; Toni Bakhtiar; Jaenal Effendi (University of Merdeka Malang, 2009)
In this paper we attempted to answer a fundamental question whether banking systembased on a profi t-loss sharing (PLS) could improve welfare than an interest based banking system bydeveloping a rigorous theoretical modeling. In the framework of production technology we fi rstlyshowed that under production certainty and competitive market both PLS and interest based systemswere effi cient and right. However, under an uncertain situation due to a productivity shock,we proved that only the PLS system was right. We verifi ed our result by quantifying the effects onincome distribution for both lender and borrower. Two indicators, namely the standard error of distributionand Gini ratio were considered. We showed that the conventional credit market led to aserious income distribution problem where lenders did not enjoy the variability in income and didnot bear any risk, but in contrast, borrowers bore all the risk. On the other side, PLS system sharedthe risk between lenders and borrowers. In the end of the analysis, we proposed an instrument thatwould improve the performance of a PLS system from lenders perspective by introducing a so-calledrisk pooling mechanism.